Modeling and Simulation of Triple Coupled Cantilever Sensor for Mass Sensing Applications - Nalluri Siddaiah; D.V. Rama Koti Reddy; Y. Bhavani Sankar; R. Anil Kumar; Hossein Pakdast (Institute of Advanced Engineering and Science, 2015)
Cantilever sensors have been the growing attention in last decades and their use as a mass detector. This work presents design, modeling and analysis of Triple coupled cantilever(TCC) sensor using MEMS simulation software Comsol Multiphysics with critical dimensions of 100μm length,20μm width and 2μm thickness. Simulations were performed based on finite element modeling techniques, where different resonant frequencies were observed for different modes of operation. It is also observed that the resonant frequency of the sensor decreases as some mass is applied on one particular cantilever. The various parameters greatly affecting the performance of TCC such as resonant frequency, dimensions, material and pressure or force applied on it.we also observed that while adding some mass on any one lateral cantilever, the resonant frequency of that respective mode reduced.